Solid particle number emissions of 56 light-duty Euro 5 and Euro 6 vehicles. (January 2022) - Lähde, Tero; Giechaskiel, Barouch; Pavlovic, Jelica; Suarez-Bertoa, Ricardo; Valverde, Victor; Clairotte, Michaël; Martini, Giorgio
Abstract: Vehicle exhaust solid particle number emissions >23 nm (SPN23) and >10 nm (SPN10) were studied for 56 market light-duty vehicles with over 1000 laboratory tests. The studied vehicle-types were gasoline port-fueled injection (PFI), gasoline direct injection (GDI), GDI with gasoline particulate filter (GPF-GDI), and diesel equipped with particulate filter (DPF) vehicles. GDI and DPF SPN emissions decreased with improving emission standards, while PFI did not. When all SPN data was considered, the emissions of GDI were the highest, followed by PFI, then DPF and GPF-GDI. However, considering the vehicles complying with the recent European regulation (Euro 6c or later), the PFI vehicles had the highest emissions amongst the studied vehicle types, often exceeding the current European SPN23 limit of 6·10 11 1/km. although the limit is not applicable to them. In addition, PFI-vehicles had the highest average sub-23 nm fraction of the studied vehicle types at all SPN23 levels. For all of the vehicle types, SPN emissions increased at low ambient temperatures. While for GDI and PFI, the sub-23 nm fraction decreased at low temperatures, for DPF vehicles it increased. Highlights: Particle number emissions from Port Fuel Injection gasoline vehicles are on average higher compared to other technologies. Cold start PN emissions are higher compared to the rest of the cycle. Emissions at low ambient temperature results in higher emissions. Cold start sub-23 nm particle emissions of diesel and gasoline direct injection vehicles have different behavior.